IoT intelligent fan / Muhamad Adam Syafi Mohamed Amir - Mohamed Amir, Muhamad Adam Syafi (2024)
This project addresses the demand for energy-efficient and convenient cooling solutions by creating an IoT- based intelligent fan with human presence detection, which allows automatic fan speed adjustment based on the presence of person in the room. The goal of this project is to design an IoT-based intelligent fan that can detect human presence and change its speed automatically for improved energy efficiency and convenience. This report aims to design a intelligent fan that will conserve energy using Arduino Microcontroller. If any human presence is detected, the fan will be turned on while maintaining a specific speed according to the room temperature and all of the current status such as ‘Motor ON’, current temperature and fan speed will be displayed on LCD. Based on the simulation and the hardware build, shows that this project is convenient for human and electricity usage can be decreased. This project provides everybody a convenient cooling solution as the weather currently is very high and this project could likely decrease the chance of getting heatstroke by a margin. Further enhancements can be investigated for future development, and the system's functioning can be improved